PENGEMBANGAN KONSEP SEKOLAH ALAM SELAMA BELAJAR DARI RUMAH DI LEMBAGA PENDIDIKAN ANAK USIA DINI - Fikri, Mohammad Tsaqibul (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2021)
Covid-19 pandemic has affected almost all aspects of human life. The education world in Indonesia is no exception, where since the establishment of covid-19 as a pandemic, the government issued the Minister of Education and Culture Circular No. 4 of 2020 which stipulates the rules for learning from home or BDR for PAUD school students. This study aims to reveal the development of the concept of a natural school in the process of physical motor development of early childhood at KBIT Al Hikmah Kebonturi - Bojonegoro, with research focuses including; 1) the application of the concept of the natural school during BDR, 2) the physical motor development of children at KBIT Al Hikmah Kebonturi, and 3) the success rate of applying the concept of the natural school in the process of physical motor development of early childhood at KBIT Al Hikmah Kebonturi. This research belongs to the type of qualitative research. From the results of data analysis, the following conclusions were drawn: 1) The application of the concept of a natural school at KBIT Al Hikmah Kebonturi uses activities outside the classroom. By utilizing the plantation environment around the school building or the home page of students and teachers. 2) The application of the concept of a natural school during BDR is still considered to be able to stimulate children's physical motoric development so that they are achieved according to their age stages. Despite the pandemic, children still get stimulation services as they should get. This can be known by the parents from the results of the child's learning reports or report cards.